FREQUENCY OF SOMATIC SYMPTOMS IN PATIENTS PRESENTING WITH MAJOR DEPRESSIVE DISORDER (The Research of Medical Science Review, 2025)
Objective: This study analyzes how frequently somatic symptoms occur among Major Depressive Disorder (MDD) patients with a focus on the relationship between symptom intensity and depression severity. Study Design: Cross-sectional study Methodology: This cross-sectional study was conducted at the psychiatry OPD, Dr. Ruth K.M. Pfau Civil Hospital, Karachi, over six months. A sample of 186 newly diagnosed MDD patients (aged 18–60 years) was selected via nonprobability consecutive sampling. Data were collected using the Hamilton Depression Rating Scale (HAMD) and Patient Health Questionnaire-15. Frequencies were calculated, and the association between MDD severity and somatic symptoms was analyzed using the chi-square test (p<0.05). Result: A total of 186 participants were included with 122 females (65.6%) at a mean age of 37.12 years. Among the participants, 89.2 percent were married and 39.8 percent were unable to read or write. A large proportion of psychiatric patients experienced severe fatigue and weakness as somatic problems according to assessment results. The severity of depression showed direct relationships with somatic complaints through assessments using HAMD-17 scores (p < 0.005). Examination of sampled subgroups through post-stratification methods demonstrated how gender distribution along with marital status and educational levels present meaningful associations. The high prevalence of suicidal thoughts among female participants along with their increased rate of concentration problems demonstrates why feminine-focused intervention is critically important. Conclusion: Patients who had MDD demonstrated a direct relationship between depression intensity and physical symptoms where fatigue alongside weakness stood out as their primary somatic issues. Treatment outcomes will improve when interventions incorporate gender-sensitive approaches that simultaneously treat psychological needs alongside somatic manifestations.